2015
DOI: 10.3892/ol.2015.3962
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and developments of immunotherapies in osteosarcoma

Abstract: Abstract. Osteosarcoma (OS) is a frequently observed primary malignant tumor. Current therapy for osteosarcoma consists of comprehensive treatment. The long-term survival rate of patients exhibiting nonmetastatic OS varies between 65-70%. However, a number of OS cases have been observed to be resistant to currently used therapies, leading to disease recurrence and lung metastases, which are the primary reasons leading to patient mortality. In the present review, a number of pieces of evidence provide support f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 118 publications
0
42
0
1
Order By: Relevance
“…Osteosarcoma has a high incidence of one to three per million every year in children and adolescents [3, 4]. Currently, the 5-year survival rate of osteosarcoma patients is quite low, especially in the patients insensitive to chemotherapy [4-6]. Although new targeting drugs have been developed in these years, side effects and poor response still disturb the osteosarcoma patients [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma has a high incidence of one to three per million every year in children and adolescents [3, 4]. Currently, the 5-year survival rate of osteosarcoma patients is quite low, especially in the patients insensitive to chemotherapy [4-6]. Although new targeting drugs have been developed in these years, side effects and poor response still disturb the osteosarcoma patients [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Like in most other cancers, immunotherapy and the so-called targeted therapies are current hot topics 7578 . As exemplified in 29 patients with refractory/relapsed osteosarcomas registered between 2009 and 2013 within the French Sarcoma Group–Bone Tumor Study Group (GSF–GETO) who received 33 treatment lines of targeted therapies, off-label use is already quite common 79 .…”
Section: Future Outlookmentioning
confidence: 99%
“…These drugs may be used alone or in combination . Recently, immunologic checkpoint blockade and targeted therapy have emerged as potentially promising therapeutic tools . Moreover, the treatment with Listeria monocytogenes , an intracellular bacterium, expressing a chimeric human HER2/neu construct to induce HER2/neu‐specific immunity, suggests that immunotherapy associated with carboplatin chemotherapy reduces pulmonary metastatic disease and prolongs survival in dogs with HER2 + appendicular OSA …”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recently, immunologic checkpoint blockade and targeted therapy have emerged as potentially promising therapeutic tools. 11 Moreover, the treatment with Listeria monocytogenes, an intracellular bacterium, expressing a chimeric human HER2/neu construct to induce HER2/neu-specific immunity, suggests that immunotherapy associated with carboplatin chemotherapy reduces pulmonary metastatic disease and prolongs survival in dogs with HER2 + appendicular OSA. 12 Canine appendicular OSA studies showed that animals which underwent amputation and received carboplatin had a higher survival rate than animals that received only surgical treatment.…”
Section: Introductionmentioning
confidence: 99%